Effects of different forage proportions in fermented total mixed ration on muscle fatty acid profile and rumen microbiota in lambs - Liu, Mingjian; Wang, Zhijun; Sun, Lin; Wang, Yu; Li, Junfeng; Ge, Gentu; Jia, Yushan; Du, Shuai (Frontiers in Microbiology, 2023)
The objectives of this study were to evaluate the effects of different forage types in fermented total mixed ration (FTMR) on growth performance, fatty acid profile, and rumen microbiota of lambs. Thirty 6-month-old Small tail Han sheep × Ujumqin lambs with initial body weight (BW) of 27.8 ± 0.90 kg were selected for the test, and divided into two groups of 15 sheep each treatment (three pens per treatment and five lambs per pen). The lambs have received 350g/kg oat (OH), and 350g/kg alfalfa (AH) diets on a dry matter basis, respectively. The results revealed that no statistically significant (p > 0.05) differences were found in dry matter intake and average daily gain between the two diet groups. The cholesterol and intramuscular fat were obviously (p < 0.05) higher in the AH group, while no statistically significant difference (p > 0.05) was found in pH24 value. The muscle fatty acid compositions of lambs were obviously (p < 0.05) influenced by the diet treatments. Compared with the OH group, the C16:1, C17:0, and C20:3n6 contents were obviously higher (p < 0.05) in the AH group, whereas the content of C18:1n9c, C20:1, C18:3n3, and C22:6n3 was obviously (p < 0.05) increased in the OH group. The MUFA contents were significantly higher in the OH group, whereas no significant differences (p > 0.05) were detected both in SFA and PUFA contents among the two diets treatments. The bacterial composition was apparently separated into two clusters based on the principal coordinate analysis, and the OH group increased the shannon index. The relative abundance of the Rikenellaceae_RC9_gut_group in the genes level was obviously (p < 0.05) increased in the AH group and the relative abundance of Prevotella_1, Fibrobacter, Bacteroidales_UCG_001_unclassified were obviously (p < 0.05) enriched in the OH group. Integrated correlation analysis also underscoring a possible link between the muscle fatty acid compositions and significantly altered rumen microbiota. Overall, these findings provide a potential insight into the diets affects fatty acid profile, and rumen microbiome of lambs, which may help make decisions regarding feeding.